A Note on Mechanical Properties, of Pinus insularis - Sekhar, A. C.; Rawat, N. S. (Indian Forester, 1960)
Mechanical tests were done in Green and Dry condition on standard dear specimens obtained from ten scantlings of Pinus insularis, received from the Divisional.Forest Officer. Balipara forest division, N.E.F. Agency. The results have been compared with teak. Pinus excelsa, Pinus insignis and Pinus roxburghii.